Analysis of CaCO3 Impregnation on HY Zeolite Surface Area, Pore Size, and Activity in the Catalytic Cracking of Palm Oil to Biofuels - Rosyad Adrian Febriansyar; Teguh Riyanto; I. Istadi (Diponegoro University, 2022)
Fossil energy sources are currently decreasing, requiring the development of alternative energy sources. Vegetable oil is a raw material for alternative renewable energy supplies. This study produced biofuels from vegetable oil using calcium carbonate (CaCO3)-impregnated HY catalysts. In addition, this study aimed to investigate the effect of CaCO3 impregnation on the surface area and the catalytic activity of catalysts in the palm oil cracking process to produce biofuels. The HY catalyst was modified by the wet impregnation method in 5 wt% CaCO3 solution and was further calcined at 550°C for three h. Furthermore, the catalysts were tested in a continuous fixed-bed catalytic reactor at 450°C. The catalyst properties were characterized using Brunauer–Emmett–Teller (BET) surface area, Barrett–Joyner–Halenda (BJH) for pore size distribution, and X-Ray Diffraction (XRD) for crystal structure and phases. The results showed that the addition of CaCO3 decreased surface area and pore volume; however, the pore size increased, which resulted in the production of heavy hydrocarbons. Interestingly, the introduction of CaCO3 enhanced the yield of Organic Liquid Product (OLP) and diesel-range hydrocarbons selectivity to reach 79.09% and 30.54%, respectively. Furthermore, the introduction of CaCO3 increased deoxygenation activity.